Prevalence and influencing factors of anxiety, depression, and burnout among teachers in China: a cross-sectional study - He, Lulu; Huang, Lingling; Huang, Yuanyuan; Li, Hehua; Zhang, Ziyun; Li, Junhao; Lin, Shisong; Wu, Kai; Huang, Dongchang; Wu, Fengchun (Frontiers in Psychiatry, 2025)
BackgroundTeachers are more likely to experience mental health issues than the general population, yet few studies focus on Chinese teachers. After the “Double Reduction” policy, teacher workload and stress have risen significantly. In Dongguan, a city actively implementing educational reforms, teacher mental health may be particularly concerning. Anxiety, depression, and burnout are prevalent mental health issues. This study examined the prevalence and factors linked to anxiety, depression, and burnout among Dongguan teachers.MethodsA cross-sectional survey evaluated the mental health of primary and secondary school teachers in Dongguan, China, using two-stage random sampling. Eleven schools were randomly selected, with 30 teachers chosen from each of 330 invited participants, 313 completed the survey (94.8% response rate), and 259 valid responses were retained after excluding incomplete or inconsistent answers. The study used the Zung Self-Rating Anxiety Scale (SAS), Zung Self-Rating Depression Scale (SDS), and Maslach Burnout Inventory-Educators Survey (MBI-ES). Wilcoxon rank-sum and Kruskal–Wallis tests identified factors linked to anxiety, depression, and burnout. Variables with p ≤ 0.10 in univariate analysis were included in multivariate logistic regression, with cut-offs of 50 for SAS, 53 for SDS, 27 for Emotional Exhaustion (EE), 13 for Depersonalization (DP), and 31 for Personal Accomplishment (PA). A p ≤ 0.10 threshold was used to avoid omitting potential predictors.ResultsThe study found anxiety, depression, and burnout prevalence rates of 19.3%, 34.7%, and 74.5%, respectively (95% CI: 14.5–24.1; 28.9–40.6; 69.2–79.9). Junior high school teachers (OR = 0.47) and those with higher education (OR = 0.39) had a lower depression risk. Female teachers (OR = 1.96) had a higher risk of emotional exhaustion (EE), while older teachers (OR = 0.923) had a lower risk of reduced personal accomplishment (PA). Anxiety and depersonalization (DP) showed no significant associations.ConclusionThe study found high rates of depression and burnout among teachers, influenced by educational level, school type, sex, and age. Authorities should address these issues by clarifying teacher responsibilities, providing mental health training, and establishing monitoring systems. As a cross-sectional study, it cannot determine causality, and further longitudinal research is needed to confirm these findings.